A moda como instituição social no contexto belo-horizontino na década de 1980: a contribuição do grupo mineiro de moda na promoção de identidades e subjetividades - Carla Alessandra Carvalho de Queiroz Braga (2015)
The dialogue between urban lifestyle and fashion is presented in this work. It offers a historical perspective that chronologically identifies the experiences and changes in consumer habits in Belo Horizonte in the range of one hundred years, since its inauguration in 1897 until the end of 1990 decade. Fashion is studied as a social institution that relates to the city backdrop in their economic, social and cultural perspectives. The activities of the Grupo Mineiro de Moda (fashion group from Minas Gerais), exponent of the social institution of fashion in Belo Horizonte during the 1980 and 1990 decades, concludes this work.